Upaya Guru Meningkatkan Minat Belajar Siswa Sekolah Dasar melalui Metode Demonstrasi materi Keterampilan Berwudhu - Melianti Melianti; Mus Mulyadi (Jurnal Indonesia Pendidikan Profesi Guru, 2025)
Background: Students’ interest in learning, especially in practical religious subjects such as ablution skills, often tends to be low when traditional teaching methods are applied. An engaging and hands-on approach is needed to increase student motivation and involvement. Objective: This study aims to increase elementary school students' interest in learning through the application of the demonstration method in teaching ablution skills. Method: This research is a Classroom Action Research (CAR) conducted in 2023 at State Elementary School 09 Ipuh, Mukomuko Regency. The sample consisted of 20 fourth-grade students. Data were collected through observation and tests, then analyzed using predetermined formulas focusing on the completeness of student learning outcomes. Result: The findings showed that the use of the demonstration method improved students' interest and performance in learning ablution skills. In Cycle II, all students achieved learning scores above the Minimum Completeness Criteria (MCC), indicating increased interest and understanding. Conclusion: The demonstration method is effective in enhancing student engagement and mastery of ablution material in elementary school settings. Contribution: This study provides practical insights for educators, particularly in Islamic education, by demonstrating that the demonstration method can significantly improve student interest and learning outcomes in skill-based religious content.